Impact of Emerging Technologies on Legal Frameworks: A Multidisciplinary Perspective - Kumar Srivastava, Ratnesh; Bhattacharjee, Rituparna; Midha, Raina; Pal Singh, Vijay; Mukherjee, Ayesha; Verma, Alok (Journal of Neonatal Surgery, 2025)
Unprecedented difficulties to present existing legal systems have come from the rapid development of new technologies such artificial intelligence, block chains, biotechnology, and the Internet of Things. Conventional legal systems often fail to change with the times, leading to jurisdictional complexity, ethical questions, and legal gaps. This paper investigates how new technologies change legal rules, government structures, and enforcement policies using a multi-modal approach. Emphasizing the need of adaptable legislative policies, it examines important domains including data privacy, intellectual property, liability, and human rights. Using insights from law, ethics, and technology studies, this study underlines the need of adaptive and progressive legislative reforms to address the issues of a developing digital environment.